2016
DOI: 10.1007/s11307-016-0959-4
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Tumor-Specific Molecular Targets in Pancreatic Adenocarcinoma: Paving the Way for Image-Guided Pancreatic Surgery

Abstract: PurposeThe purpose of this study was to identify suitable molecular targets for tumor-specific imaging of pancreatic adenocarcinoma.ProceduresThe expression of eight potential imaging targets was assessed by the target selection criteria (TASC)—score and immunohistochemical analysis in normal pancreatic tissue (n = 9), pancreatic (n = 137), and periampullary (n = 28) adenocarcinoma.ResultsIntegrin αvβ6, carcinoembryonic antigen (CEA), epithelial growth factor receptor (EGFR), and urokinase plasminogen activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 120 publications
0
51
0
Order By: Relevance
“…Integrin avb6 has been shown to be a promising target for identification of PDAC, and differentiation with pancreatitis and normal pancreatic tissue, with retained expression in vital tumor cells after neoadjuvant therapy (12)(13)(14)(15)30). Nowadays, the majority of patients will receive neoadjuvant therapy prior to surgery due to late onset of symptoms and therefore, presentation with locally advanced disease, or borderline resectable tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin avb6 has been shown to be a promising target for identification of PDAC, and differentiation with pancreatitis and normal pancreatic tissue, with retained expression in vital tumor cells after neoadjuvant therapy (12)(13)(14)(15)30). Nowadays, the majority of patients will receive neoadjuvant therapy prior to surgery due to late onset of symptoms and therefore, presentation with locally advanced disease, or borderline resectable tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, out of a panel of different biomarkers, we selected integrin avb6 as the most promising target for pancreatic cancer detection, based on its potential to discriminate tumor and inflammation, to identify lymph node metastases, and to differentiate between viable tumor cells and necrosis in patients who received neoadjuvant therapy (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In search of other tumor‐specific imaging targets, de Geus et al found that CEA, integrin αvβ6, epithelial growth factor receptor and urokinase plasminogen activator receptor seem suitable targets for pancreatic imaging . In this study, 158 of 165 (96%) of pancreatic and periampullary adenocarcinomas could be identified using CEA immunohistochemistry.…”
Section: Cea and Pancreatic Cancermentioning
confidence: 64%
“…In this study, only 6 of 20 tissues showed homogeneous CEA expression and 15 of 20 tissues showed expression in >50% of neoplastic pancreatic cells. Previous studies reported CEA expression in approximately 60% to 75% of PDAC tissues 3,18. Serum CEA measurements were performed using the Elecsys CEA assay (Roche Diagnostics), which is previously described to be specific for CEACAM5 as well as for NCA-2, the nonspecific cross reacting antigen-2 19.…”
Section: Discussionmentioning
confidence: 99%